The Robot Factory Pseudoscience in Education and Its Threat to American Democracy - Ganem, Joseph; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
Fake Science Is Killing Our Schools$1 (Band Our Republic Science is both a method for understanding and a guide for decision-making. It can and should be the foundation for citizenship: logic, reasoning, challenging claims, making choices based on verifiable fact. Authentic science education is key to producing informed, engaged citizens. It can't be separated from the culture in which it operates. Instead, we're in the most vicious cycle imaginable for a democracy$1 (Bbut perfect for a corporatist kleptocracy. With agenda-driven leaders using pseudoscience to justify bad educational policy, education has become a dehumanizing tool for mass producing compliant workers who accept what they're told and do what they're asked. Physicist and educator Dr. Joseph Ganem rips the lid off of this neatly-packaged scam. He exposes the dangers of pseudoscience in the hands of decision-makers, educators, and students. In nothing less than a compelling new vision for 21st century education, he calls us to reject pseudoscience in all forms, engage in a collective search for truth, and commit to an authentic education for every child. (3z(BDr. Ganem nails it! He brings a scientist$1 (Bs eye and a crusader$1 (Bs passion to explaining how (3z(Breformers(3y (Bare killing an education system that once was$1 (Band still could be$1 (Bthe envy of the world.(3y (B--John Owens, author, Confessions of a Bad Teacher: The Shocking Truth from the Front Lines of American Public Education (3z(BEmpowering and enlightening. Sparks will fly when people read this book - so policymakers be forewarned (or better be ready)! There will be a revolution - a powerful call for change." --CJ Westerberg, Founder & Editor, The Daily Riff: Be Smarter. About Education.s
Introduction -- Why I Would Fail Third Grade Math: A Multitude of Problems in One Brief Lesson -- Data-Driven Education Reform: A New Pseudo-science -- Science: Motivation, Measurement, and Meaning -- The Scientific Method Misapplied to Education -- The (3z(BMathematical Intimidation(3y (Bof Teachers -- The Statistical Impossibility of Adequate Yearly Progress in Schools -- The SAT: Promoting equal opportunity or perpetuating a hierarchy? -- The Accountability Hoax -- Facts versus Stories -- Why Our Kids Don$1 (Bt Get Math -- The Widening Gap Between High School and College Math -- The Disconnect Between the Math Curriculum and Professional Practitioners -- Making Math Relevant: Assessing reading comprehension or math? -- The (3z(BChinese Room(3y (B-- Misunderstanding Science Education -- Why Science is Hard -- Science as a Noun -- Science as a Question -- Science as a Conversation -- Science as a Guide -- Science as a Verb -- The Limits of Science -- Having It Both Ways -- Teachers are Real Human Beings (Not Idealized Fantasy People) -- The Teacher-Student Relationship -- The Opposite of Science: Elevating Complexity -- Impossible Expectations -- Across Time and Space: The complex web of human relatedness -- Do Adults Model the Educational Values They Espouse? -- False Choice: The dark side of storytelling -- Schools are not Cultural Islands -- Dismembering Literature to Avoid its Truths -- The Fallacy of Market-based Education Reforms -- Markets: Meaning and Morality -- Education Markets: The Higher-Ed debacle -- The Charter School Movement -- The Logical Fallacies Embedded in the (3z(BBusiness Model(3y (B-- The Paradox of Wealth: Towards an Expanded Understanding of Self-Interest -- Rethinking Education -- Back to the Future: The (3z(BDeficit Model(3y (Bof Education -- Transformative Education -- Beyond the Business Model -- Rethinking College: Preparing for the Unimagined -- The Expectations Trap -- The Limits of Education -- The Overlooked Role of Questions and Reflection -- Being Educated -- Knowing and Understanding -- Do Computers Understand? -- Relatedness -- The Real Crisis -- A Call to Action.s
Keywords: Mathematics; Education and state; Educational tests and measuremen; Popular Science in Education; Mathematics Education; Education Policy; Assessment, Testing and Evaluation